The Association of Bacterial Vaginosis with Gynecologic Complaints and Clinical Data - Işık, Gözde; Küçük, Ayşegül; Demirezen, Şayeste; Beksaç, Mehmet Sinan; Hasçelik, Gülşen (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVES: To investigate the relationship between Bacterial vaginosis (BV) and various gynecologic complaints or clinical data. STUDY DESIGN: Cervico-vaginal smears from 200 patients were examined by both cytologic and microbiologic methods in view of BV. Gynecologic complaints were also completed for each woman and these data were recorded on the computer for statistical analysis. RESULTS: Thirteen cases (6.5%) were diagnosed as BV both by cytological and microbiological techniques. These cases were accepted as a study group. Cases without infectious agents (n=187) were the control group. There was a significant correlation between the presence of BV and some parameters such as fishy odor vaginal discharge and abortion( p<0.05), but there was no significant difference between BV and other complaints, such as irregular menstrual cycle, abnormal vaginal bleeding, hormone replacement therapy, myoma, operation or usage of IUD (p>0.05). CONCLUSION: The type and odor of vaginal discharge and abortion play important role for correct detection of BV cytologically and microbiologically. Awareness of these findings warn not only the gynecologist examining the patients but also the cytopathologist.